KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU (Studi Kasus Guru-Guru SD Negeri di Kecamatan Kandeman) - Muh Budiyanto, 12.5202.0123; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine the role of the principal leadership in moderating the influence of motivation and job satisfaction of the teachers performance. Population and sample are teachers of elementary schools in the Kandeman district.The data were obtained by distributing 147 pieces questionnairs,but only 144 are processed because 3 questionnairs were not returned by the respondents.Statistical testing  data include:: validity test with factor analysis techniques, normality test, hyterokesdastisitas test, reliability test using Cronbach's alpha formula, determination test,  F test, statistical t test and effect moderation test.The results of this study states that: (1) motivation has significant effect on teacher performance (2) job satisfaction has significant effect on teacher performance (3) Principals Leadership has significant role, in moderating the motivation on the teacher performance and (4) the principal leadership has significant role, in moderating the job satisfaction effect on the teacher performance. Keywords: the principal leadership,motivation, job satisfaction,teacher performance